Editorial for Vol. 34, No. 4 - Juwon Lim (Hanggong uju uihakoeji)
This issue features three papers in aerospace medicine, including one original article and two reviews, focusing on cardiovascular health, vestibular illusions, and diabetes management in aviation. The first study investigates cardiovascular health during flight phases using a wearable device. Results show significant heart rate changes during the landing phase, reflecting increased workload and sympathetic activation. However, the study’s scope is limited to a single pilot, warranting further research. The second paper reviews vestibular illusions in military aviation, highlighting their role in spatial disorientation, which accounts for 5% of military aviation accidents with a 90% fatality rate. It emphasizes training, including virtual reality simulation, to mitigate risks, but lacks specific data on effectiveness. The third paper compares diabetes management protocols for aviation personnel in Korea, the United States of America, Australia and International Civil Aviation Organization. Korea restricts insulin-dependent pilots, while other countries allow limited operations with advanced glucose monitoring. The paper advocates for updated domestic guidelines reflecting international practices.